2014
DOI: 10.1002/hec.3124
|View full text |Cite
|
Sign up to set email alerts
|

Does Physician Dispensing Increase Drug Expenditures? Empirical Evidence from Switzerland

Abstract: This paper analyzes whether the opportunity for physicians to dispense drugs increases healthcare expenditures. We study the case of Switzerland, where dispensing physicians face financial incentives to overprescribe and sell more expensive pharmaceuticals. Using comprehensive physician-level data, we exploit the regional variation in the dispensing regime to estimate causal effects. The empirical strategy consists of a doubly-robust estimation that combines inverse probability weighting with regression. Our m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 34 publications
2
34
2
Order By: Relevance
“…Collectively, over-prescribing raised consultation costs through an increase in the total time of treatment. Therefore, the authors concluded that dispensing by physicians clearly affects health care expenditures hence placing an additional burden on the patients and healthcare system [2]. In line to what is reported earlier, Beck et al by using the canton-level data reported that physician dispensing considerably increases drug expenditures [15].…”
Section: Dispensing Separation and Medication Costmentioning
confidence: 67%
See 2 more Smart Citations
“…Collectively, over-prescribing raised consultation costs through an increase in the total time of treatment. Therefore, the authors concluded that dispensing by physicians clearly affects health care expenditures hence placing an additional burden on the patients and healthcare system [2]. In line to what is reported earlier, Beck et al by using the canton-level data reported that physician dispensing considerably increases drug expenditures [15].…”
Section: Dispensing Separation and Medication Costmentioning
confidence: 67%
“…Inline to the inefficiencies of the healthcare systems around the globe, dispensing separation has been a topic of thoughtful interest in the literature [2][3][4][5][6]. While some countries allow physicians to dispense medicines, a number of OECD (Organization for Economic Co-operation and Development) countries have fully banned physician dispensing of medications to the patients [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using physician-level data for the period 2008-10, and exploiting regional variation in dispensing regimes across cantons, Kaiser and Schmid (2013) show that dispensing physicians (40% of the total) increase drug costs per patient by 30%. However, several other studies have shown that self-dispensing doctors have a mitigating cost-saving effect by prescribing generics more frequently where their profit margins are higher (Rischatsch et al, 2009).…”
Section: Source: Oecd Health At a Glance 2015mentioning
confidence: 99%
“…However, while the separation of prescription and sale of drugs is suitable in most regions, factors such as geography or population density can justify self-dispensation. Even though self-dispensation has been shown to potentially increase general drug expenditures (Kaiser and Schmid, 2015), the aim to ensure optimal medical and pharmaceutical coverage can weigh higher than the additional costs. Though it may help particular regions to allow for self-dispensing physicians, it is obvious that a single person who pools complex competences is a second-best solution to two distinct specialists: a pharmacist with her background in chemistry and pharmacy and a doctor with her background in medicine.…”
Section: Introductionmentioning
confidence: 99%